2016
DOI: 10.1080/15548627.2016.1221565
|View full text |Cite
|
Sign up to set email alerts
|

Brain trauma and autophagy: What flies and mice can teach us about conserved responses

Abstract: Drosophila models have been successfully used to identify many genetic components that affect neurodegenerative disorders. Recently, there has been a growing interest in identifying innate and environmental factors that influence the individual outcomes following traumatic brain injury (TBI). This includes both severe TBI and more subtle, mild TBI (mTBI), which is common in people playing contact sports. Autophagy, as a clearance pathway, exerts protective effects in multiple neurological disease models. In a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…We found that TBI in flies shares key characteristics with TBI in mammals, including temporary incapacitation, short-term ataxia, progressive neurodegeneration, intestinal barrier dysfunction, hyperglycemia, and shortened lifespan ( Katzenberger et al 2013 , 2015a ). Furthermore, consistent with findings of an activated Nuclear Factor kappa B (NF-κB) response in mammals, transcriptional gene targets of the homologous NF-κB-mediated Toll and Immune-deficiency (Imd) signaling pathways are rapidly and persistently activated following TBI in multiple fly models ( Katzenberger et al 2013 , 2015a , 2015b 2016; Barekat et al 2016 ; Ratliff et al 2016 ; Sen et al 2017 ; Shah et al 2019 ). For example, expression of major Toll and Imd gene targets, antimicrobial peptides (AMPs), substantially increases within 30 min after TBI and remains elevated for at least 24 h ( Katzenberger et al 2016 ).…”
supporting
confidence: 71%
See 1 more Smart Citation
“…We found that TBI in flies shares key characteristics with TBI in mammals, including temporary incapacitation, short-term ataxia, progressive neurodegeneration, intestinal barrier dysfunction, hyperglycemia, and shortened lifespan ( Katzenberger et al 2013 , 2015a ). Furthermore, consistent with findings of an activated Nuclear Factor kappa B (NF-κB) response in mammals, transcriptional gene targets of the homologous NF-κB-mediated Toll and Immune-deficiency (Imd) signaling pathways are rapidly and persistently activated following TBI in multiple fly models ( Katzenberger et al 2013 , 2015a , 2015b 2016; Barekat et al 2016 ; Ratliff et al 2016 ; Sen et al 2017 ; Shah et al 2019 ). For example, expression of major Toll and Imd gene targets, antimicrobial peptides (AMPs), substantially increases within 30 min after TBI and remains elevated for at least 24 h ( Katzenberger et al 2016 ).…”
supporting
confidence: 71%
“…In flies, both closed-head and penetrating TBI leads to increased expression of AMP genes in fly heads ( Katzenberger et al 2016 ; Ratliff et al 2016 ; Sanuki et al 2019 ). However, the source of this expression is not known because fly heads contain multiple cell types, including neurons, glia, and fat body, all of which are known to express AMPs ( Cao et al 2013 ; Kounatidis et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Neuronal damage and apoptosis are important pathological process in SBI after ICH. It has also been shown that autophagy is activated after ICH and endoplasmic reticulum (ER) stress occur in neurodegenerative diseases . And autophagy may play different role36s in ischemic and hemorrhagic stroke .…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 ROS are also important factors in autophagy. 8 Although research has shown that cellular autophagy can lead to neurodegeneration or neuronal dysfunction, 9 the molecular mechanisms of neuropathic pain are still unknown.…”
Section: Introductionmentioning
confidence: 99%